Zircon geochronology and O-Hf isotopes of Cappadocian ignimbrites: new insights into continental crustal architecture underneath the Central Anatolian Volcanic Province, Turkey - Akin, Lütfiye; Aydar, Erkan; Schmitt, Axel Karl; Çubukçu, H. Evren; Gerdes, Axel (Gondwana research, 2021)
During the Mio-Pliocene between ca. 10 and 5 Ma, the Central Anatolian Volcanic Province (CAVP) formed as the focus of a high eruptive flux episode with voluminous high-silica, caldera-forming eruptions. Magmatic compositions of ignimbrites emplaced during this episode were uniformly rhyodacitic-rhyolitic, reflecting melt generation in an intracrustal hot zone heated by intrusions of basalt that were extracted from fertile asthenospheric mantle undergoing decompression. The clear imprint of crustal rocks on CAVP magmas provides unique opportunity to constrain the deep crustal architecture of central Anatolia. Here, we present a detailed study of zircon from key CAVP ignimbrites including U-Pb ages and the first coupled O- and Hf-isotopic compositions for this silicic igneous province, along with complementary whole-rock Nd isotope data. Ignimbrites with higher δ18O and lower εHf values (Zelve, Cemilköy, Gördeles) are typically compositionally more evolved compared to those with intermediate (Kavak, Kızılkaya) and more mantle-like compositions (Sarımadentepe, Sofular, Tahar), which is consistent with magmas acquiring their isotopic compositions through crustal assimilation coupled with fractional crystallization. Intriguingly, O-Hf-zircon compositions from Kızılkaya ignimbrite, one of the largest and youngest CAVP eruptions, cover almost the same isotopic range than all CAVP ignimbrites collectively. Despite evidence for a significant crustal influence revealed by O-Nd-Hf isotopic compositions of CAVP ignimbrites, inherited zircon is absent in all units. This is in stark contrast with previous studies of Kızılkaya ignimbrite for which abundant Proterozoic-Archean zircon populations have been reported. Isotopic compositions of evolved magmas in the CAVP can be explained by interaction of mantle-derived basalt with post-Archean crust, with minor contributions of hydrothermally altered rocks. No tangible evidence exists for a magmatic contribution of Archean crustal components to the Mio-Pliocene ignimbrite flare-up in Central Anatolia, suggesting that regional basement rocks largely represent Gondwanan crust that was originally consolidated and subsequently became reprocessed during post-Archean times.
Online verfügbar: 11 Dezember 2020
Gesehen am 13.07.2021